The Selection of Energy Storage in the Southern Sulawesi Electricity System with AHP-TOPSIS Method - Peri Indriyanto; Vita Lystianingrum (Department of Electrical Engineering ITS and FORTEI, 2025)
In the fourth quarter of 2023, a power deficit of up to 600 MW was observed in the Southern Sulawesi (Sulbagsel) electricity system due to the prolonged El Nino that affected hydropower plants. Based on the 2021-2030 RUPTL, the Sulbagsel system does not allow the addition of renewable energy (RES) plants, except with a battery firming scheme while the construction of fossil-based power plants is also limited by the government. One potential mitigation strategy for PLN (Perusahaan Listrik Negara) is to evaluate the potential application of Energy Storage Systems (ESS) in the Sulbagsel system. The purpose of this research is to evaluate the selection of ESS in the South Sulawesi electricity system through a combination of AHP (Analytical Hierarchy Process) and TOPSIS (Technique for Order of Preference by Similarity to Ideal Solution). The AHP-TOPSIS method is an optimal choice for this evaluation due to its capacity to address complex evaluation scenarios by considering a multitude of comprehensive criteria and conducting weighting analyses to ascertain accuracy and identify optimal solutions. The evaluation criteria encompass technical, economic, environmental, and social considerations, with a total of 15 subcriteria. The alternatives to be evaluated are PHES (Pumped Hydro Energy Storage), BESS (Battery Energy Storage System), and HESS (Hydrogen Energy Storage System). The results of the evaluation demonstrate that PHES is the optimal alternative, with a preference value of 0.68. BESS is ranked second with a preference value of 0.33, while HESS is ranked third with a preference value of 0.20.